2019
DOI: 10.3121/cmr.2018.1452
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Isolated Unilateral Glossopharyngeal Nerve Palsy

Abstract: Isolated palsy of the glossopharyngeal nerve is rare. We report the case of an elderly patient with unilateral right glossopharyngeal nerve palsy secondary to extra cranial ischemia. On examination there was no other deficit other than an absent right gag reflex. She was diagnosed clinically with ischemic stroke of the ninth nerve, and her daily dose of aspirin was increased from 81 mg to 325 mg. Magnetic resonance imaging of the brain showed a normal brainstem and cerebellum with patent intracranial circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Bilateral facial nerve palsy is a relatively rare GBS presentation but has been observed in some cases [ 5 ]. There have also been rare cases of glossopharyngeal nerve palsy secondary to CN ischemia and GBS, especially the PCB variant [ 6 ]. However, bilateral involvement of the glossopharyngeal nerve secondary to GBS has never been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral facial nerve palsy is a relatively rare GBS presentation but has been observed in some cases [ 5 ]. There have also been rare cases of glossopharyngeal nerve palsy secondary to CN ischemia and GBS, especially the PCB variant [ 6 ]. However, bilateral involvement of the glossopharyngeal nerve secondary to GBS has never been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…It was rarely reported but it has not been analysed in correlation with PSD. [11][12][13][14][15] There are no reports in the literature on a correlation between diabetes and moderate and severe PSD according to PAS. 16 This study is the first attempt to evaluate diabetes as a risk factor for PSD confirmed with FEES with emphasis to silent aspiration (SA) as a high risk of AP.…”
Section: Introductionmentioning
confidence: 99%
“…The glossopharyngeal nerve (CN IX) provides motor, sensory, and parasympathetic innervation to the tongue, pharynx, and hypopharynx and functions to elevate the larynx and pharynx during swallowing 3,4 . Glossopharyngeal palsy is characterized by dysphagia, impaired gag reflex, parotid gland dysfunction, and reduced sensation over the posterior tongue and pharynx 5,6 . A multi-institutional study found 1 hypoglossal nerve injury after posterior cervical laminectomy and no cases of glossopharyngeal nerve palsy 1 .…”
mentioning
confidence: 99%